Relationship amongst off-ice and on-ice speed and agility measures in men and women Division III ice hockey players - Curro, A. D.; Pierce, H.; Visich, P. S.; Rosene, J. M. (Journal of Athletic Enhancement, 2017)
Ice hockey is a team sport that requires players to perform at high intensity for a short duration (~ 30 to 45 seconds), thereby necessitating anaerobic conditioning. Off-ice performance measures have long been used for ice hockey players however their usefulness has been debated. This has resulted from potential differences in muscle recruitment, metabolic cost, and level anaerobic conditioning to name a few.